Penerapan Media Quizizz sebagai Alat Evaluasi Pembelajaran Teks Artikel di Kelas XII SMA Negeri 1 Semarang - Alfiyani Nur Safitri; Asep Purwo Yudi Utomo; Mu’allimatin Najihah; Sahrul Mubarok; Arka Yanitama; Eva Wulandari; Ani Wahyuni (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
One of the important stages in learning is evaluation. From the evaluation carried out, information will be obtained regarding the learning development of students which will be used in making decisions. The success of the learning process and student learning outcomes will also be known through evaluation. In learning Indonesian, a learner will proceed to acquire diverse knowledge and learning experiences. One of the basic competencies that must be mastered by class XII in the 2013 curriculum is that students are able to analyze the structure and language rules of article texts. One of the evaluation tools that can be used in the Quizizz application. The Quizizz application is in the form of online lectures that students can access via the web which can show statistical data on student performance. The results of these data can help educators and students in evaluating learning. The application of the Quizizz application can be an option in carrying out evaluation activities for learning article text in class XII IPS 1 SMA Negeri 1 Semarang. Quiziz is a tool for obtaining data related to student learning processes and outcomes. This study aims to describe the application of the Quizizz application as a learning evaluation tool for class XII article texts at SMA Negeri 1 Semarang. This research was conducted using a qualitative descriptive method. Data collection techniques using observation, interviews, and documentation. The results obtained from this study are the use of Quiziz as an evaluation tool in learning article texts in class XII which is suitable to be applied because apart from being easy to access and attracting the attention of students in working on questions, educators can also carry out assessments or evaluations more quickly because they have been automatically provided by the system.